A small share in history a Quaker initiative in Eastern Europe - Lampen, Diana; Lampen, John (<<The>> Hope Project, 2013)
This booklet describes a Quaker initiative visiting Belarus and Ukraine between 1991 and 2004, as they emerged from the Soviet Union, sharing methods of creative conflict handling in schools and inter-active classroom approaches; and working in Croatia, Macedonia and Bosnia and Herzegovina from 1996 to 2012 with civil society groups which were trying to forge a positive way forward after the civil wars